STRUX shelf / Nur Syuhada Rosli - Rosli, Nur Syuhada (Universiti Teknologi MARA, Kedah, 2018)
STRUX shelf is a structure design with combination material plywood and metal rod. The concept of biophilic for Clever and multifunction, STRUX shelf eventually become integrated into the adult's use as a plant shelf and storage compart-ment. The influence of design from Malay Ginger as a reference shape. The shape design that has been stylized uniquely to show a symbolization of high character shelf storage the book, the newspaper even can plant the flower.